The Governance of Interorganizational Networks: An Analysis of the Tension Between Efficiency and Inclusiveness in the Decision-Making Process - Schmidt, Joel Ricardo Rocha; Wegner, Douglas; Fortes, Marcos Vinícius Bitencourt (REGEPE Entrepreneurship and Small Business Journal, 2019)
Objective: To analyze how the critical contingency factors of interorganizational network governance - trust, number of members, goal consensus and network level competency needs - described by Provan and Kenis (2008), influence the tension between decision-making process and inclusion of decision-makers. Method: The research followed a qualitative approach based on multiple case studies in Small and Medium Sized Enterprises. Data were collected through interviews, documentary analysis and observation. Originality / Relevance: The research contributes to the discussion about the role of critical contingency factors and their relationship with the tension between efficiency and inclusion in the decision-making process of networks. The originality of the study refers to the empirical evidence about the role of these factors in that tension. Results: Results shows the role of critical contingency factors, the mechanisms used for tension management, and the identification of two additional contingency factors: trust in network management and the geographical dispersion of its members. Theoretical / methodological contributions: The study contributes to the literature through empirical evidence in that it shows that the critical contingency factors influence the tension between efficiency and inclusion of the decision process. In addition, it has been identified two additional factors: trust in management and geographic dispersion. Social / management contributions: Based on the results analysis, it was identified that granting greater autonomy to the executive managers of the networks and their internal teams and valuing the moments of contact with the members to ensure participation are recommended mechanisms for the management of the studied tension.